Acknowledging privilege in an intentional community while working with adolescents in residential treatment. Issue 1 (2nd April 2020) - Kelly, Sarah
ABSTRACT: In this original narrative the author describes her experience living in an intentional community of volunteers the year after she completed her undergraduate studies. The author and her fourteen community members served in a residential treatment center in Chicago, IL that worked with youth who were experiencing trauma and marginalization. The author's experience of living in an intentional community and serving a group of 17 to 20-year-old young men allowed her to acknowledge her own privilege and learn what it means to use privilege to advance the well-being of those who are underserved.